Assessing iron overload: Are we there yet? - Kruger, P.; Leahy, M.; Olynyk, John (American Association Cancer Research, 2012)
Iron overload occurs in many hematologic disorders and causes significant morbidity. The advantages of MRI in quantifying liver iron concentration continue to mount, and the association between iron overload and increased mortality after allogeneic stem cell transplant needs further attention.